A generation of change, a lifetime of difference? : Social policy in Britain since 1979 - Evans, Martin, 1957- (Book collections on Project MUSE., 2009)
This original book provides an overview of changes in social and fiscal policy since the 1970s, using an original and unique lifetime simulation approach to analyse how changes in these policies would affect people of low median and high income living in 1979, 1997 and 2008 if they lived their whole lives under the policy rules in place in these years.